Pengaruh Media Typewriter Alphabet Digital Berbantuan Audio Visual untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Sekolah Dasar - Wahyuni; Munir Yusuf; Mirnawati (South Sulawesi Education Development, 2024)
This research aims to determine the effect of using audio-visual assisted digital alphabet typewriter media to improve the initial reading ability of grade 1 students at SDN 23 Batara. The type of research used in this research is Pre-Experimental Design with a One-Group Pretest-Posttest Design research design. The population of this study was all grade 1 students at SDN 23 Batara. The sample consisted of 26 people. The collected data was processed using descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive analysis, the average value (pretest) was 66.85 and the average value (posttest) was 90. Meanwhile, based on the results of inferential statistical analysis, t-test results were obtained with a significant value (2 tailed) <0.05, namely < 0.000 means H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a significant influence between the application of audio-visual assisted digital alphabet typewriter media on the beginning reading ability of grade 1 students at SDN 23 Batara.